OPTIMALISASI STRATEGI PEMASARAN UNTUK MENINGKATKAN POPULARITAS DAN KINERJA LAYANAN KURSUS MENGEMUDI - Andi Ashabul Kahfi; Sandy Sandy (Politeknik STIA LAN Makassar, 2026)
The rapid development of the service sector, particularly driving training, has driven the need for promotional strategies relevant to current digital trends. As a new institution in Makassar City, the Annailah Driving Course faces challenges in building popularity amidst intense competition. This study aims to examine the effectiveness of promotional videos through Instagram content as a strategic medium in increasing the institution's presence. The method used is a descriptive qualitative approach, with data collection through interviews, observation, documentation, and literature review. The object of the study was the Instagram account @kursus_mengemudi_annailah, which was analyzed before and after the creation of an educational promotional video. The results showed that the use of videos with educational narratives, engaging visuals, and formats that suit Instagram's characteristics significantly increased digital interaction. The number of video views increased from 564 to 1,928, while engagement levels such as likes and comments also experienced a sharp increase. These findings reinforce the theory that visual communication through video is an effective marketing strategy in building the institution's popularity and image. In conclusion, Instagram can be a potential promotional medium for non-formal educational institutions, provided there is consistent content management. Recommendations from this study include the development of a regular content strategy, as well as exploring other digital platforms such as TikTok and YouTube to reach a wider audience.